Assessment of Textural Differentiations in Forest Resources in Romania Using Fractal Analysis - Andronache, Ion; Fensholt, Rasmus; Ahammer, Helmut; Ciobotaru, Ana-Maria; Pintilii, Radu-Daniel; Peptenatu, Daniel; Draghici, Cristian-Constantin; Diaconu, Daniel Constantin; Radulovic, Marko; Pulighe, Giuseppe; AZIHOU, AKOMIAN FORTUNÉ; TOYI ALAGBE, S. SCHOLASTIQUE MIREILLE; et al. (My University, 2017)
Deforestation and forest degradation have several negative effects on the environment including a loss of species habitats, disturbance of the water cycle and reduced ability to retain CO2, with consequences for global warming. We investigated the evolution of forest resources from development regions in Romania affected by both deforestation and reforestation using a non-Euclidean method based on fractal analysis.We calculated four fractal dimensions of forest areas: the fractal box-counting dimension of the forest areas, the fractal box-counting dimension of the dilated forest areas, the fractal dilation dimension and the box-counting dimension of the border of the dilated forest areas. Fractal analysis revealed morpho-structural and textural differentiations of forested, deforested and reforested areas in development regions with dominant mountain relief and high hills (more forested and compact organization) in comparison to the development regions dominated by plains or low hills (less forested, more fragmented with small and isolated clusters). Our analysis used the fractal analysis that has the advantage of analyzing the entire image, rather than studying local information, thereby enabling quantification of the uniformity, fragmentation, heterogeneity and homogeneity of forests.
Keywords: fractal analysis; forest resources; forest management; box-counting method; deforestation